Relevance Of Negotiation As Alternative To Violence In Resolving Deep-Rooted Conflict - Amos Ojo Adedeji (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The emergence of negotiation an Alternative Dispute Resolution (ADR) mechanism in resolving conflict is gradually gaining ground in Africa. It is very much effective today in resolving interactive and long standing conflict. This study examines the relevance of negotiation as alternative to violence in resolving deep-rooted conflict. Despite negotiation potency to amicably resolve deep-rooted conflict, the study revealed some noticeable challenges hindering its relevancy such as cultural sensitivities, adversarial attitude of legal representative and absence of national negotiation/ADR law. The paper concluded by recommending among other things cultural pluralisation, legal representative attitudinal change and drafting of national negotiation/ADR Act